Antimicrobial susceptibility patterns of Staphylococcus aureus causing cellulitis among adult patients attending clinical services at Kiruddu Referral Hospital, Kampala. A cross-sectional study. - Nteziyaremye, Jorome; Oromcan , Benjamin W; Kasozi, James; Duluga, Seldon; Mabonga , Habert (Student's Journal of Health Research Africa, 2025)
Background Staphylococcus aureus is responsible for most cases of cellulitis infections. Cellulitis is the most common bacterial infection on the skin surfaces in humans all over the world. The study aims to investigate the AST patterns of Staphylococcus aureus that cause cellulitis in adult patients. Methods A cross-sectional study analyzed 279 wound swabs from cellulitis patients at Kiruddu Referral Hospital, Kampala. Samples were cultured on Mannitol Salt, Blood, and MacConkey Agars. Staphylococcus aureus was identified by Gram stain, catalase, and coagulase tests; other isolates (Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae) were confirmed biochemically. Antimicrobial susceptibility was determined using Kirby-Bauer disk diffusion on Mueller-Hinton agar, interpreted per CLSI (2023) guidelines. Susceptibility frequencies were calculated with Microsoft Excel. Results Among 279 patients, 56.3% of the participants were female, and 31.5% were aged 36–45 years. 50.5% were married, and 30.5% had completed secondary education. Staphylococcus aureus was the predominant pathogen (56.6%, n=158). Of these, 43.7% were methicillin-resistant (MRSA). Susceptibility to key antibiotics was: vancomycin (96.8%), quinupristin/dalfopristin (81.6%), clindamycin (73.4%), and trimethoprim-sulfamethoxazole (64.6%). Streptococcus pyogenes showed high penicillin susceptibility (90.0%), while Gram-negative isolates exhibited significant resistance to commonly used antibiotics. Conclusion High MRSA prevalence and significant antibiotic resistance were found, necessitating routine susceptibility testing and strengthened stewardship to guide effective cellulitis treatment Recommendation The Ministry of Health should incorporate TB LAM Ag test strips into the national HIV/TB diagnostic guidelines, especially for patients with advanced immunosuppression.